Conquest of Sustainable Development through Reformative Mechanisms of ADR - Tharakan, Rachel Jacob; Lahoti, Kanika (European Journal of Sustainable Development, 2019)
An ever booming world population in the recent years have made a significant impact on the environment and a proportional rise in environmental issues. Amicable dispute settlement in environmental conflicts seem a far-fetched dream with the vastly different judicial systems of countries worldwide and thus, there exists a need for reinventing dispute resolution mechanisms to achieve the Sustainable Development Agenda. Goal 16 of the Sustainable Development Agenda calls for peace, justice and strong institutions and in furtherance of the same, The United Nations Environment Programme have discussed Alternative Dispute Resolution in Environmental Disputes as a part of Access to Justice. Like any other system, ADR also has its barriers to practical implementation. Moreover on a philosophical level, it is significant to question the ethics of environmental ADR as a form of restorative justice. With the help of this paper, the authors aim to examine and reconcile the identified benefits and issues of environmental ADR while focusing on the aspect of sustainable development. The authors also aim at evaluating the effectiveness of ADR on a global level and bring out the practicality of the mechanism in the same domain before concluding the paper with derived and intended suggestions. Keywords: Alternate Dispute Resolution Mechanism, Environmental Conflict, Sustainable Development, United Nations Environment Programme